Engineering plasticity - Calladine, C. R. (Commonwealth and international library. Structures and solid body mechanics division., 1969)
Engineering Plasticity deals with certain features of the theory of plasticity that can be applied to engineering design. Topics covered range from specification of an ideal plastic material to the behavior of structures made of idealized elastic-plastic material, theorems of plastic theory, and rotating discs, along with torsion, indentation problems, and slip-line fields. This book consists of 12 chapters and begins by providing an engineering background for the theory of plasticity, with emphasis on the use of metals in structural engineering; the nature of physical theories; and the conce.